Accuracy of full-guided versus half-guided implant procedures carried out with digital implant planning software by students as part of a university curriculum - Daniel Einsiedel; Stephanie Knapp Giacaman; Anna Seidel; Lara Berger; Mayte Buchbender; Manfred Wichmann; Ragai Edward Matta (BMC Medical Education)
Abstract Background This in vitro study investigated whether full-guided (FG) or half-guided (HG) implant placement is more suitable for beginners and to what extent the use of the coDiagnostiX (CDX) (10.5, Straumann Group, Basel, Switzerland) implant planning software proves useful in teaching. Methods Twenty students planned implant positions with CDX which were then placed in a model using printed drill templates in the sense of FG implantation (group 1) and HG implantation (group 2). The implant positions could be compared with those of the reference model, and deviations could be determined. The results were tested for significance using the t-test for independent samples for groups 1 and 2. A total of 32 students subsequently completed a questionnaire about the software. Cronbach's α was also calculated to check the reliability of the questions for the individual subject areas. Results In both groups the greatest deviation occurred along the y-axis in the vestibular direction. It measured 1.390 mm in group 1 and 1.570 mm in group 2. Comparing both groups, there were significant deviations along the y-axis (p = .013), along the z-axis (p = .049), and in the total deviation (p = .031). The questionnaire was evaluated in design, with 95% positive answers. In contrast, the evaluation of the area of time and effort resulted in only 55% positive responses. Overall, experience with the software was rated as positive by 74%. Conclusions Group 1 achieved more accurate results, especially along the y-axis in the vestibular direction. In both groups, the implants were placed too deep. The questionnaire indicated a software with high usability and is therefore very suitable for teaching. If clinically feasible, beginners should prefer full-guided implant placement.